2013
DOI: 10.1017/s0022215113002259
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising otitis externa: clinical profile and management protocol

Abstract: A high index of suspicion, early diagnosis and prompt intervention are key factors to decrease morbidity and mortality. Fluoroquinolones, third generation cephalosporins and surgical debridement are the mainstay of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
2
20
1
Order By: Relevance
“…This supports our data and our conclusions [9] . Our mortality rate is significantly lower (2.4%) than that of other studies (14.8%), possibly due to the fact that these patients are managed jointly with infectious diseases [5] .…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…This supports our data and our conclusions [9] . Our mortality rate is significantly lower (2.4%) than that of other studies (14.8%), possibly due to the fact that these patients are managed jointly with infectious diseases [5] .…”
Section: Discussioncontrasting
confidence: 74%
“…In common with other studies, the most common causative organism was P. aeruginosa, but other organisms, such as S. aureus, are increasingly prevalent in these patients [5,10] . A French study of 32 cases of necrotizing otitis externa found that mean length of stay (18.2±8.7 vs. 11.6±6.9 days, p=0.03) and duration of antibiotic therapy (9.4±3.2 vs. 5.8±0.7 weeks, p<0.001) were significantly lower after 2009 when a management protocol for necrotizing otitis externa was introduced.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…9 This increase seems to be related to an increasing elderly population, and the increase in the incidence of diabetes. This condition is frequently clinically challenging, 10,11 and clinical teams may have to devote more time to the management of affected patients.…”
mentioning
confidence: 99%